Considerations for Treating Generalized Pustular Psoriasis (GPP): A Narrative Review - Lynde, Charles W.; Prajapati, Vimal H.; Gooderham, Melinda J.; Hong, H. C.; Kirchhof, Mark G.; Lansang, Perla; Ringuet, Julien; Turchin, Irina; Vender, Ron; Yeung, Jensen; Papp, Kim A. (Université d'Ottawa | University of Ottawa, 2025)
Abstract Generalized pustular psoriasis (GPP) is a rare, chronic dermatological condition characterized by widespread pustulation that may be associated with other cutaneous and systemic manifestations. If left untreated, it may be life-threatening. Therapies developed for plaque psoriasis have been used to treat GPP with limited efficacy; however, these therapies do not target the interleukin (IL)-36 pathway, which is the most common pathway implicated in the pathogenesis of GPP. A systemic biologic targeting the IL-36 receptor for the treatment of GPP is currently the only approved treatment for GPP and allows for an opportunity to improve patient outcomes. This manuscript outlines practical considerations that aim to provide guidance on personalizing the treatment of GPP.